Prevalence, Severity, and Determinant Factors of Anemia among Pregnant Women in South Sudanese Refugees, Pugnido, Western Ethiopia - Aklilu Alemayehu; Lealem Gedefaw; Tilahun Yemane; Yaregal Asres (Anemia)
Background. Anemia is one of the major health problems among refugee pregnant women in the world. Anemia among pregnant women is multifactorial and results in detrimental consequences on the mothers and infants. The aim of this study was to determine the prevalence, severity, and determinants of anemia among pregnant women in South Sudanese refugees, Pugnido western, Ethiopia. Methods. A facility-based cross-sectional study was conducted in Pugnido Administration Refugee and Returnee Affairs Health Center from April 15 to June 30, 2015. Demographic and related data were collected using questionnaire based interview. Complete blood count was done using CELL-DYN 1800 (Abbott USA). Blood smear and fecal specimen were examined for hemoparasite and intestinal parasite, respectively. Bivariate and multivariate logistic regression analyses were done using SPSS-Version 20.0. Results. The overall prevalence of anemia was 36.1%, from whom 2.3% had severe anemia. Being in third trimester, eating meat at most once a week, drinking tea immediately after meal at least once a day, having mid-upper arm circumference below 21 centimeters, and intestinal parasitic infection were identified as independent factors of anemia. Conclusion. More than one-third of pregnant women had anemia in this study. Intervention based strategies on identified determinant factors will be very important to combat anemia among the group.